Penggunaan Media Pembelajaran Powtoon untuk Meningkatkan Hasil Belajar Menggambar Komik Siswa Kelas VIII.5 MTs Negeri 3 Padang - Suriyani, Sri; Hafiz, Abd. (Lembaga Yasin AlSys, 2023)
This study aims to determine the increase in student learning outcomes in the material for drawing comics using powtoon learning media in class VIII.5 students of MTsN 3 Padang. The type of research used in this research is classroom action research (CAR). This research was carried out in two cycles, each cycle having two meetings. Methods and data collection tools in this study are in the form of observation, tests, and documentation. Data analysis in this study was by t-test using SPSS version 26. The results obtained in this study indicate that using powtoon learning media can improve learning outcomes in arts and culture in comic drawing materials for class VIII.5 MTsN 3 Padang. In the pre-cycle the average value obtained was 73.28 and then continued by carrying out cycle II the average student learning outcomes increased by 86.21. Thus it can be concluded that the use of powtoon learning media can improve the learning outcomes of drawing comics for class VIII.5 students of MTsN 3 Padang.